2021
DOI: 10.1016/j.pmedr.2021.101486
|View full text |Cite
|
Sign up to set email alerts
|

Rural community systems: Youth physical activity promotion through community collaboration

Abstract: Highlights A community systems approach is important to identify social and geographic health impacts. Community stakeholders residing within the city had higher trust and collective efficacy scores. These stakeholders had roles directly leading physical activity opportunities for youth. Youth physical activity was greater in the community with stakeholders in administrative roles. Unique community variables should be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…While there were no significant differences in MVPA in terms of grade and race, the results indicate the overall daily average minutes of MVPA to be lower than recommended levels for this population. A recent population PA surveillance study also found that females and particularly middle school females (i.e., sixth grade) reported lower levels of PA than males [ 16 , 17 ]. Furthermore, our study indicated that there were no statistically significant PA levels based on age/grade level.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While there were no significant differences in MVPA in terms of grade and race, the results indicate the overall daily average minutes of MVPA to be lower than recommended levels for this population. A recent population PA surveillance study also found that females and particularly middle school females (i.e., sixth grade) reported lower levels of PA than males [ 16 , 17 ]. Furthermore, our study indicated that there were no statistically significant PA levels based on age/grade level.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the varying start times of each program site and to avoid issues with variability due to seasonality to ensure proper estimates of MVPA behavior, all participating sites had to complete the YAP instrument during the academic school year. Similar population surveillance studies followed similar protocols and analyzed descriptive patterns at the population level during an academic school year [ 15 , 16 ].…”
Section: Methodsmentioning
confidence: 99%
“…95 However, little is known about the most effective ways to engage different kinds of communities (e.g., low income vs high income and rural vs urban) in CSPAPs, though there is emerging research in this area of investigation. 96,97 A notable gap is the lack of evidence about how to work collaboratively with local governments to effect policy change and increase accountability for CSPAP implementation.…”
Section: Examples Of Cspap Researchmentioning
confidence: 99%
“…For example, Snavely and Tracy [17] show in their study that leaders have difficulties in sustaining collaborations due to a permanent lack of local funding and geographical distances. According to Kellstedt et al [16], trust between cooperative partners within a community tends to develop in more peripheral areas with dense settlements. One explanation is that in such communities the likelihood of multiple (random) encounters between the members involved increases, as work and private life are not geographically far apart.…”
Section: Trust In Rural Areasmentioning
confidence: 99%
“…To prevent the further decline of services of general interest, it is crucial to strengthen regional cooperation and social networks [14]. Empirical findings show that trust is an important component in the development of regional cooperation structures [15][16][17]. It is important to foster trust between inter-organisational actors to strengthen cultural networks and cooperation, which at the same time also secures cultural education infrastructures and thus cultural engagement.…”
Section: Introductionmentioning
confidence: 99%